Development of high performance casting analysis software by coupled parallel computation - Sang Hyun CHO; Jeong Kil CHOI (China Foundry, 2007)
Up to now, so much casting analysis software has been continuing to develop the new access way to real casting processes. Those include the melt flow analysis, heat transfer analysis for solidification calculation, mechanical property predictions and microstructure predictions. These trials were successful to obtain the ideal results comparing with real situations, so that CAE technologies became inevitable to design or develop new casting processes. But for manufacturing fields, CAE technologies are not so frequently being used because of their difficulties in using the software or insufficient computing performances. To introduce CAE technologies to manufacturing field, the high performance analysis is essential to shorten the gap between product designing time and prototyping time. The software code optimization can be helpful, but it is not enough, because the codes developed by software experts are already optimized enough. As an alternative proposal for high performance computations, the parallel computation technologies are eagerly being applied to CAE technologies to make the analysis time shorter. In this research, SMP (Shared Memory Processing) and MPI (Message Passing Interface) (1) methods for parallelization were applied to commercial software "Z-Cast" to calculate the casting processes. In the code parallelizing processes, the network stabilization, core optimization were also carried out under Microsoft Windows platform and their performances and results were compared with those of normal linear analysis codes.